Hydrogen production for energy: An overview. (7th February 2020) - Dawood, Furat; Anda, Martin; Shafiullah, G.M.
Abstract: Power to hydrogen is a promising solution for storing variable Renewable Energy (RE) to achieve a 100% renewable and sustainable hydrogen economy. The hydrogen-based energy system (energy to hydrogen to energy) comprises four main stages; production, storage, safety and utilisation. The hydrogen-based energy system is presented as four corners (stages) of a square shaped integrated whole to demonstrate the interconnection and interdependency of these main stages. The hydrogen production pathway and specific technology selection are dependent on the type of energy and feedstock available as well as the end-use purity required. Hence, purification technologies are included in the production pathways for system integration, energy storage, utilisation or RE export. Hydrogen production pathways and associated technologies are reviewed in this paper for their interconnection and interdependence on the other corners of the hydrogen square. Despite hydrogen being zero-carbon-emission energy at the end-use point, it depends on the cleanness of the production pathway and the energy used to produce it. Thus, the guarantee of hydrogen origin is essential to consider hydrogen as clean energy. An innovative model is introduced as a hydrogen cleanness index coding for further investigation and development. Graphical abstract: Image 1 Highlights: Innovative hydrogen cycle model proposed of a square-shaped Hydrogen Square (HydS). Innovative HPP categorising model proposed to describe the H2 production pathways. . The cost of the hydrogen purification must be added to the hydrogen cycle feasibility. The guarantee of hydrogen origin is essential to ensure its energy cleanness. An innovative hydrogen cleanness index model has been introduced.